Influence of macroeconomic factors on Malaysian stock returns - Khairul Najihah, Yusof (2015)
This paper studies macroeconomic factors that influence stock market in Malaysia. Macroeconomic factors used in this study are money supply, inflation, oil price, exchange rate and industrial production index. Meanwhile, Malaysian stock market returns studied are FTSE Bursa Malaysia KLCI (FBM KLCI) and FTSE Bursa Malaysia EMAS Index (FBM EMAS Index). The findings showed only three macroeconomic variables are significantly influenced FBM KLCI while the rest two are not significant. Meanwhile, for FBM EMAS Index, all macroeconomic variables are not significantly influenced except for money supply. However, both stock returns show the same relationship which is only inflation has positive influences while the rest four variables are negatively influence. Lastly, the financial crisis 2008 indicates that there is no significant impact on this study.